2021
DOI: 10.1177/10820132211049603
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antifungal activity of essential oils of clove, lemongrass and thyme for natural preservation of dried apricots

Abstract: Currently, the majority of fresh apricots destined for the production of dried apricots undergo sulphur oxide fumigation before drying to protect the fruit against fungal spoilage. To eliminate the use of sulphite, packaging assisted with essential oil is a promising strategy to increase shelf-life of dried apricots since it does not impact its flavor characteristics. In this study, three essential oils were selected: clove, lemongrass and thyme. They were screened for antifungal activity against Eurotium spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Syzygium aromaticum showed beneficial advantages in antibacterial and antifungal activity, aromaticity and safety, especially against a wide range of food-borne microorganisms, making it a potential and valuable preservative in the food industry. The antifungal activity of clove is superior to that of lemongrass and thyme essential oils to prevent the natural preservation growth of fungi on dried apricots (122). Ju et al (123) confirmed by accelerated storage tests that the CEO can extend the shelf life of food bakery products by 2-4 days under normal packaging.…”
Section: Food Storagementioning
confidence: 99%
“…Syzygium aromaticum showed beneficial advantages in antibacterial and antifungal activity, aromaticity and safety, especially against a wide range of food-borne microorganisms, making it a potential and valuable preservative in the food industry. The antifungal activity of clove is superior to that of lemongrass and thyme essential oils to prevent the natural preservation growth of fungi on dried apricots (122). Ju et al (123) confirmed by accelerated storage tests that the CEO can extend the shelf life of food bakery products by 2-4 days under normal packaging.…”
Section: Food Storagementioning
confidence: 99%